2000
DOI: 10.1002/(sici)1099-1212(200001/02)10:1<65::aid-oa505>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Perimortem processing of human remains among the Great Basin Fremont

Abstract: The perimortem butchering of human remains has been proposed for many sites in the Anasazi Culture Area of the southwestern United States at around ad 1000. This paper presents evidence that similar practices occurred in an adjacent culture area to the north. A cluster of Fremont sites in south‐central Utah show evidence of this same processing pattern including scalping, dismemberment, cooking, and fracturing of long bones. The material from one of these Fremont sites, Backhoe Village, is presented to illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…The taphonomic principles for recognizing cannibalism in the archaeological record developed by Turner and Turner (1999), Villa (1992), and White (1992) have been applied successfully to other sites in the American Southwest (cf. Billman et al 2000;Hurlbut 2000;Lambert et al 2000), the Great Basin (Novak and Kollman 2000), the Arctic (Melbye and Fairgrieve 1994), the Pacific (Degusta 2000), and Europe (Caceres et al 2007), albeit with some detractors (Bullock 1991; Darling 1999;Dongoske et al 2000;Ogilvie and Hilton 2000). Moreover, such principles have been applied to extremely old hominine remains from Spain and France (Defleur et al 1999;Diez et al 1999;Fernandez-Jalvo et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The taphonomic principles for recognizing cannibalism in the archaeological record developed by Turner and Turner (1999), Villa (1992), and White (1992) have been applied successfully to other sites in the American Southwest (cf. Billman et al 2000;Hurlbut 2000;Lambert et al 2000), the Great Basin (Novak and Kollman 2000), the Arctic (Melbye and Fairgrieve 1994), the Pacific (Degusta 2000), and Europe (Caceres et al 2007), albeit with some detractors (Bullock 1991; Darling 1999;Dongoske et al 2000;Ogilvie and Hilton 2000). Moreover, such principles have been applied to extremely old hominine remains from Spain and France (Defleur et al 1999;Diez et al 1999;Fernandez-Jalvo et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…In these cases, special measures may be required to keep these individuals from returning to cause harm to the living (Lee & Vaughan, 2008). In North America ( ad 700–1300), it has been suggested that assemblages containing partial, dismembered remains with evidence of cut marks and heat damage may be the result of witch killings (Hurlbut, 2000; Martin, 2016; Novak & Kollman, 2000). In the United Kingdom ( ad 1200–1400), similar modifications have been interpreted as efforts to prevent the rise of revenant corpses (Mays et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To support arguments for cannibalism, human remains should also display modifications which are virtually identical to those found in animal bone assemblages (Morales-Pérez et al, 2017;Villa, Courtin, & Helmer, 1988;White, 1992). Although the remains from Kabusanza display tool marks consistent with butchery and fragmentation, these do not appear with the same frequency (11.9%) or degree of fragmentation that has been observed in 'cannibalized' assemblages, where in excess of 40% of fragments show some form of modification (Bello et al, 2016;Novak & Kollman, 2000;Turner & Turner, 1999). They also differ from modifications identified in animal bone assemblages from eastern Africa.…”
Section: Humerusmentioning
confidence: 95%
“…One way archaeologists identify anthropophagy is by studying the processing and cooking of human osteological remains. Novak and Kollmann (2000) analyzed human remains from the Fremont culture area in south-central Utah, dating to around AD 1000, and found that human bones were processed and cooked just like animal meat for consumption. Evidence for capturing, killing, and processing human bodies at the Sacred Ridge settlement in the early AD 800s comes from a combined analysis of the butchering patterns on the bones, human remains on a metate, and a cooking jar that contained human myoglobin (Kuckelman 2016).…”
Section: Cooking and Ritualmentioning
confidence: 99%